Color terms for black and their semantic development in Ashaninka and Asheninka language - Solari Ruiz-Eldredge, Oscar Augusto (2019)
The main purpose of this research is the analysis of kisaari, cheenkari, potsitari and ponaari, terms that belong to black-color notion in Ashaninka and Asheninka language, and are the result of the codification of the perception of jumping aspects of various referents of nature, showed in the opacity presented by its structure. Their reconstruction is grounded in lexicalization theory and their belonging to the category, in the theory of basic color terms and that of prototypes. The results show that kisaari was built from the dark aspect of a seed species; cheenkari, from the appearance of blackish spots of a snake species; potsitari, from the appearance of a reddish-blackish natural dye, and ponaari, from the comparison of the swelling of a body with the physical appearance of the area of the injured skin.